Determinación de hormonas tiroideas y su incidencia en el exceso de peso en adultos, de 20- 45 años de la comunidad Baldramina, cantón Quevedo Los Ríos primer semestre 2015 - Calderón Reinado, Jean Manuel (2015)
Thyroid hormones influence the main metabolic pathways. Its most obvious and known action is increased basal energy expenditure that acts on the protein, carbohydrate and lipid metabolism. With specific reference to the lipid metabolism, thyroid hormones affect the synthesis, mobilization and lipid degradation, although degradation is influenced more by the synthesis. The relationship between thyroid function and body weight in overweight individuals has become a major health concern. Several investigators have studied the effect of thyroid hormones in the body mass index (BMI), and several studies have shown that the thyroid dysfunction affects body weight With this research project we will provide data that will give us to know the prevalence of the association of thyroid dysfunction, mainly subclinical hypothyroidism in patients with overweight as it is useful to determine behavior or rules to follow in preventing complications in our patients improving the quality of life and long-term survival. After running this research will benefit all those overweight thyroid function tests are performed in the community Baldramina